Possibilités d'amélioration des porte-greffes de l'amandier par hybridation interspécifique - Grasselly C.; Olivier G. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
After having obtained the peach x almond hybrids, now the most appreciated rootstocks for almond growing, other interspecific hybrids are now being obtained and studied to solve other particular demands. They are mainly hybrids between the myrobolan plum and the almond or the peach. From these hybrids a better adaptation to soil moisture in compact soils than peach x almond hybrids is expected, but also a good vigour and a good behaviour in chlorosis inducing soils. Other hybrids with species close to peach as P. davidiana and P mira are also made, looking for resistance to Meloidogyne nematodes.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)